Optimalisasi Branding UMKM Sop Buah Pandawa melalui Promosi Digital - Nawang Cahya Ningrum; Annisa Agustin; Damayanti Damayanti (STIE Pelita Nusantara, 2026)
MSMEs are one of the sectors that have an important role in supporting the community's economy. However, many MSMEs still face obstacles in promotion and business identity development, causing product marketing to be less optimal. This community service activity was carried out at Sop Buah Pandawa MSME with the aim of increasing product sales through digital promotion. The methods used in this activity included observation, problem identification, program planning, implementation, and evaluation. The programs carried out included creating a TikTok account and promotional content, installing business banners, placing stickers on the cart, and installing tablecloths to improve the appearance of the business place. The results showed changes in the business appearance so that it looked neater, more attractive, and easier for consumers to recognize. In addition, the use of social media helped expand product promotion to the community. Based on the activities that have been carried out, branding optimization and digital promotion can help increase consumer attraction, expand product marketing, and support the development of Sop Buah Pandawa MSME to compete better with similar businesses. Keywords: MSMEs, branding, digital promotion